SF3B1 mutations in myelodysplastic syndromes: A potential therapeutic target for modulating the entire disease process - Jiang, Moqin; Chen, Meng; Liu, Qian; Jin, Zhiling; Yang, Xiangdong; Zhang, Weifeng (Frontiers in Oncology, 2023)
Myelodysplastic syndromes (MDS) are clonal hematologic malignancies characterized by ineffective hematopoiesis and dysplasia of the myeloid cell lineage and are characterized by peripheral blood cytopenia and an increased risk of transformation to acute myeloid leukemia (AML). Approximately half of the patients with MDS have somatic mutations in the spliceosome gene. Splicing Factor 3B Subunit 1A (SF3B1), the most frequently occurring splicing factor mutation in MDS is significantly associated with the MDS-RS subtype. SF3B1 mutations are intimately involved in the MDS regulation of various pathophysiological processes, including impaired erythropoiesis, dysregulated iron metabolism homeostasis, hyperinflammatory features, and R-loop accumulation. In the fifth edition of the World Health Organization (WHO) classification criteria for MDS, MDS with SF3B1 mutations has been classified as an independent subtype, which plays a crucial role in identifying the disease phenotype, promoting tumor development, determining clinical features, and influencing tumor prognosis. Given that SF3B1 has demonstrated therapeutic vulnerability both in early MDS drivers and downstream events, therapy based on spliceosome-associated mutations is considered a novel strategy worth exploring in the future.